Contribution of Household Sanitation to Acute Respiratory Infection Symptoms Among Children: Analysis of the 2017 Indonesian Demographic Health Survey - Iswanto Iswanto; Sepsiana Puspitasari; Windu Syawalina Wahyuningsih; Nurendah Ratri Azhar Rusprayunita; Furaida Khasanah; Indira Puspa Febryanti (Research and Community Service Unit, Poltekkes Kemenkes Kupang, 2025)
Acute Respiratory Infections (ARI) remain one of the primary causes of mortality among children under 5 in Indonesia, and poor inadequate drinking water, sanitation, and hygiene (WASH) conditions can exacerbated the transmission of respiratory pathogens. However, their association with ARIs in Indonesia remains underreported. This study aimed to analyze the contribution of these sanitation conditions to ARI symptoms in children under five in Indonesia. This research method was cross-sectional quantitative design study based on secondary data from the 2017 Indonesian Demographic and Health Survey (IDHS), based on secondary data from the 2017 Indonesian Demographic and Health Survey (IDHS), which was the most recent available at the time of the study. The determined sample consisted all toddlers aged 0-59 months, from women aged 15-49 years. The weighted sample that met the inclusion criteria (children aged 0-59 months, living with their parents, willing to answer questions) and exclusion criteria (missing data and